Hacking Gender and Technology in Journalism - De Vuyst, Sara (Taylor & Francis, 2020)
Hacking Gender and Technology in Journalism addresses the question of whether journalism's new digital spaces suffer from the same gendered structures as traditional media organisations, or whether they go beyond such bias. This book offers insights into the challenges that women journalists face in relation to technological innovation, as well as the potential for developing strategies for empowerment that it offers. More specifically, there is a focus on the gendering of digital skills, the construction of gender in new digital spheres of journalism, and how these changes can lead to the disruption of gender inequalities in journalism. This book will be of interest to scholars in multimedia journalism, media ethics, and gender studies.